2010
DOI: 10.1016/j.apsoil.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetles (Coleoptera: Scarabaeidae) can improve soil hydrological properties

Abstract: a b s t r a c tAlthough dung beetles are known to perform a multitude of ecosystem services, their effects on water infiltration, runoff, porosity, moisture and erosion of soil have never been thoroughly researched. Maintenance of these hydrological properties is important in agro-ecosystem functioning where overgrazing results in negative impacts on the soil. The study site was located in the Potshini catchment in KwazuluNatal (South Africa), an area heavily grazed by livestock. We conducted two rainfall simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 27 publications
1
84
0
6
Order By: Relevance
“…Temporary infestation of the digestive tract by dung beetles and 'flying away' from the anus at the time of the defaecation is termed Scarabiasis or Canthariasis 1 . In Scarabiasis, patients usually complain of loss of appetite, diarrhoea, cramps in abdomen and sometimes fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporary infestation of the digestive tract by dung beetles and 'flying away' from the anus at the time of the defaecation is termed Scarabiasis or Canthariasis 1 . In Scarabiasis, patients usually complain of loss of appetite, diarrhoea, cramps in abdomen and sometimes fever.…”
Section: Discussionmentioning
confidence: 99%
“…Dung beetles feed partly or exclusively on faeces and play a useful role in agriculture by burying and consuming dung, thereby improving the nutrient cycling and soil structure 1 . Temporary infestation of the digestive tract by dung beetles and 'flying away' from the anus at the time of the defaecation is termed Scarabiasis or Canthariasis 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Entre sus funciones más importantes, los escarabajos fertilizan el suelo (Bertone et al, 2006;Yamada et al, 2007), incrementando su aeración y porosidad (Brown et al, 2010). Son dispersores secundarios de semillas (Estrada y Coates-Estrada, 1991;Vulinec, 2002;Andresen, 2003), ayudan a promover el crecimiento del pasto (Bang et al, 2005;Arnaudin, 2012) y suprimen organismos patógenos del suelo en los pastizales (Doube et al, 1991).…”
Section: Introductionunclassified
“…Studies have shown that physical and chemical soil properties affect the diversity, structure, and reproduction of dung beetles (Arellano et al, 2008;Martínez et al, 2009;Brown et al, 2010;Arellano and Castillo-Guevara, 2014;Farias et al, 2015;. Properties such as moisture content can promote the survival and reproductive success of some dung beetle species (Sowig, 1995;Martínez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%